Indian agriculture - "Bhatia ,B.M." (New Delhi, 1988)
It is not enough to view agricultural policy in terms of the achievement of a certain growth rate in the farm sector or the attainment of national self-sufficiency in food supply and raw materials for agro-based industries. Contributing around 40 percent of the GDP and employing 67 percent of the country's labour force, agriculture remains the mainstay of Indian economy to this day. The fortunes of agriculture not only affect but actually govern the fortunes of national economy.
Keywords: Ecological and Agriculture development